Ceramic-based composite material with ultrahigh-temperature ceramic coating and preparation method of ceramic-based composite material

Through the pretreatment steps of annealing and argon ion bombardment under vacuum air atmosphere, the yttrium-doped hafnium-based metal organic frame material is introduced in combination with the brush coating method, and through physical vapor deposition and Joule thermal ultrafast synthesis process, ceramic-based composite materials with ultra-high temperature ceramic coating are produced, solving the problem of insufficient performance of traditional materials in high-temperature environments and achieving higher high temperature resistance and oxidation resistance.

CN119504287APending Publication Date: 2025-02-25AEROSPACE INST OF ADVANCED MATERIALS & PROCESSING TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411664541.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Traditional ceramic matrix composites have problems with insufficient high-temperature resistance and high-temperature mechanical properties in high-temperature environments, and it is difficult to quickly prepare uniform and dense multi-component composite coatings.

Method used

The pretreated ceramic matrix composite material was prepared by annealing under vacuum air atmosphere and bombarding with argon ion. Then, an organic solution of yttrium-doped hafnium-based metal organic frame material was introduced using a brush coating method, silicon and carbon were evaporated through physical vapor deposition method, and annealed by Joule thermal ultrafast synthesis process to produce a ceramic matrix composite material with an ultra-high temperature ceramic coating.

Benefits of technology

It improves the high temperature resistance, oxidation resistance and reusable performance of ceramic matrix composites, enhances its thermal stability and thermal shock resistance in high temperature environments, and extends its service life under multiple thermal cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005144275700000181
    Figure BDA0005144275700000181
  • Figure BDA0005144275700000191
    Figure BDA0005144275700000191
Patent Text Reader

Abstract

The invention relates to a ceramic-based composite material with an ultrahigh-temperature ceramic coating and a preparation method of the ceramic-based composite material. The method comprises the following steps: annealing the ceramic-based composite material in a vacuum atmosphere, and then bombarding the surface of the annealed ceramic-based composite material by using argon ions to obtain a pretreated ceramic-based composite material; preparing an organic solution containing the yttrium ion doped hafnium-based metal organic framework material; brushing the surface of the pretreated ceramic-based composite material with an organic solution, and annealing in a vacuum atmosphere to obtain a modified ceramic-based composite material; and evaporating silicon and carbon on the surface of the modified ceramic-based composite material by using a physical vapor deposition method, and then annealing by using a Joule heat ultrafast synthesis process to prepare the ceramic-based composite material with the ultrahigh-temperature ceramic coating. The ceramic-based composite material with ultrahigh-temperature ceramic coating protection prepared by the invention has excellent high-temperature resistance, oxidation resistance and reusability, and can be used for preparing thermal structure materials in the field of aerospace.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of aerospace materials, and in particular relates to a ceramic-based composite material with an ultra-high temperature ceramic coating and a preparation method thereof. Background Art

[0002] The structural parts of aerospace vehicles have high requirements for the high temperature resistance and high temperature mechanical properties of ceramic-based composites. Traditional ceramic-based composites that rely solely on the matrix are difficult to meet the requirements. Oxygen erosion in the environment can easily cause failure of the matrix and interface layer and fiber damage. HfC ultra-high temperature ceramics have a high melting point, excellent high temperature resistance, and certain antioxidant properties. The preparation of ultra-high temperature ceramic coatings on the surface of ceramic-based composites is expected to meet the needs of aerospace vehicle structural parts for ultra-high temperature ceramic-based composites. However, the current traditional precursor impregnation and cracking processes and chemical vapor impregnation processes are difficult to quickly prepare uniform and dense multi-component composite coatings, and the ceramic-based composites with multi-component composite coatings prepared by traditional methods have insufficient high temperature resistance and high temperature mechanical properties.

[0003] In summary, there is an urgent need to develop an efficient method for preparing ceramic-based composites with ultra-high temperature ceramic coatings. Summary of the invention

[0004] In order to solve one or more technical problems existing in the prior art, the present invention provides a ceramic-based composite material with an ultra-high temperature ceramic coating and a preparation method thereof.

[0005] In a first aspect, the present invention provides a method for preparing a ceramic-based composite material having an ultra-high temperature ceramic coating, the method comprising the following steps:

[0006] (1) annealing the ceramic matrix composite material in a vacuum atmosphere, and then bombarding the surface of the annealed ceramic matrix composite material with argon ions to obtain a pretreated ceramic matrix composite material;

[0007] (2) preparing an organic solution containing a hafnium-based metal organic framework material doped with yttrium ions;

[0008] (3) applying an organic solution to the surface of the pretreated ceramic-based composite material and annealing the pretreated ceramic-based composite material in a vacuum atmosphere to obtain a modified ceramic-based composite material;

[0009] (4) Silicon and carbon are evaporated onto the surface of the modified ceramic matrix composite material using a physical vapor deposition method, and then annealed using a Joule heat ultrafast synthesis process to obtain a ceramic matrix composite material with an ultrahigh temperature ceramic coating.

[0010] Preferably, in step (1): at a vacuum pressure of ≤10 -6Annealing is carried out in a vacuum atmosphere with a pressure of 1000 mbar and a temperature of ≥1000°C.

[0011] Preferably, in step (1): when argon ions are used for bombardment, argon gas is introduced to a working pressure, and a glow discharge is generated after the power is turned on, and the argon gas is ionized into plasma to bombard the surface of the annealed ceramic matrix composite material; argon gas is introduced to a working pressure of ≥5×10 -5 mbar; the bombardment voltage is 1.0-2.0keV, the bombardment current is 3-9mA, and the bombardment time is 5-15min.

[0012] Preferably, in step (2), the preparation of the organic solution comprises the following sub-steps:

[0013] (a) using hafnium tetrachloride as a hafnium source and terephthalic acid as an organic ligand, heating the mixture in N,N-dimethylformamide solvent to obtain a hafnium-based metal organic framework material;

[0014] (b) using ethanol to uniformly disperse the hafnium-based metal organic framework material and yttrium nitrate under ultrasonic action to obtain an organic solution containing the hafnium-based metal organic framework material doped with yttrium ions.

[0015] Preferably, in step (a): the molar ratio of the hafnium tetrachloride to the terephthalic acid is 1:(1.05-1.25); and / or the temperature of the heating reaction is 120-150° C., and the time of the heating reaction is 20-40 hours.

[0016] Preferably, in step (b): the mass ratio of the yttrium nitrate to the hafnium-based metal organic framework material is 1:(5-10).

[0017] Preferably, in step (3): the brush coating thickness of the organic solution is 100-300 μm; the annealing temperature is 500-1000° C.; the holding time at the annealing temperature is 30-90 min; and / or the heating rate to the annealing temperature is 5-10° C. / min.

[0018] Preferably, in step (4): when evaporating silicon and carbon, the molar ratio of silicon to carbon is 1:(1.1-1.3).

[0019] Preferably, in step (4): the Joule heat ultrafast synthesis process is carried out in a Joule ultrafast heating device, the heating rate is 100-150°C / s, the annealing temperature is 1000-1600°C, and the holding time at the annealing temperature is 2-10 min.

[0020] In a second aspect, the present invention provides a ceramic-based composite material with an ultra-high temperature ceramic coating, which is prepared by the preparation method described in the first aspect of the present invention.

[0021] Compared with the prior art, the present invention has at least the following beneficial effects:

[0022] (1) The present invention adopts a brush coating method to quickly introduce ultra-high temperature ceramic components (yttrium-doped hafnium carbide ultra-high temperature ceramic components) onto the surface of a substrate with the aid of hafnium-based MOFs and yttrium nitrate, wherein the presence of hafnium-based MOFs is conducive to the uniform dispersion of yttrium nitrate, thereby ensuring the formation of yttrium-doped hafnium carbide ultra-high temperature ceramic components with uniform microstructure, and the pore structure of hafnium-based MOFs is conducive to the formation of specific nanoscale and / or microscale structures, thereby facilitating the optimization of the thermophysical properties and mechanical properties of the formed ceramic components, thereby improving the high temperature resistance, oxidation resistance and reusability of the ceramic-based composite materials; It was found that the doping of yttrium will change the crystal structure of hafnium carbide (HfC), reduce the formation of lattice defects by forming a solid solution, which is beneficial to enhance the thermal stability of ceramic-based composites in high-temperature environments. In addition, in a high-temperature oxidizing environment, yttrium doping can form a dense yttrium oxide (Y2O3) protective layer, slow down the oxidation rate of hafnium carbide, and improve the oxidation resistance. In addition, yttrium doping can improve the matching of the thermal expansion coefficient of hafnium carbide (HfC), reduce thermal stress, and improve the thermal shock resistance of ceramic-based composites, thereby increasing the service life of ceramic-based composites under multiple thermal cycles.

[0023] (2) The Joule heat ultrafast synthesis process adopted in the present invention can quickly improve the ceramic sintering degree inside the coating and the bonding strength between the coating and the substrate, thereby effectively improving the protective effect of the coating on the ceramic-based composite material substrate. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0025] In a first aspect, the present invention provides a method for preparing a ceramic-based composite material having an ultra-high temperature ceramic coating, the method comprising the following steps:

[0026] (1) annealing the ceramic-based composite material (ceramic-based composite material matrix) under vacuum atmosphere, and then bombarding the surface of the annealed ceramic-based composite material with argon ions to obtain a pretreated ceramic-based composite material; the present invention does not specifically limit the type of ceramic-based composite material matrix, and those skilled in the art can conventionally select; the present invention first performs step (1) to obtain a pretreated ceramic-based composite material, and then performs the subsequent coating preparation step, because the present invention finds that annealing under vacuum atmosphere can release the residual stress generated in the ceramic-based composite material during the manufacturing and processing process, and prevent cracking or peeling caused by thermal stress during the subsequent coating preparation process, and then bombarding the surface of the annealed ceramic-based composite material with argon ions can further optimize the microstructure and chemical activity of the surface of the ceramic-based composite material, provide a high-quality adhesion interface for the subsequent coating preparation, promote the formation of the coating material on the substrate surface, and through high-energy argon ion bombardment, effectively remove the weak bonding area or microcracks on the surface, which is beneficial to improve the bonding strength of the interface between the subsequent coating and the substrate, which creates favorable conditions for improving the high temperature resistance, oxidation resistance and anti-stripping performance of the coating prepared subsequently;

[0027] (2) preparing an organic solution containing a hafnium-based metal organic framework material doped with yttrium ions (abbreviated as organic solution);

[0028] (3) brushing the organic solution onto the surface of the pretreated ceramic matrix composite material and annealing it in a vacuum atmosphere to obtain a modified ceramic matrix composite material; in the present invention, the brushing thickness of the organic solution is, for example, 100 to 300 μm; in step (3) of the present invention, the rate of heating to the annealing temperature is 5 to 10° C. / min, and the annealing time at the annealing temperature is, for example, 30 to 90 min; the present invention obtains a modified ceramic matrix composite material having an yttrium-doped hafnium carbide ultra-high temperature coating through step (3);

[0029] (4) using a physical vapor deposition method to evaporate silicon and carbon onto the surface of the modified ceramic matrix composite material (evaporating silicon and evaporating carbon simultaneously), and then using a Joule heat ultrafast synthesis process to anneal, so as to obtain a ceramic matrix composite material having an ultrahigh temperature ceramic coating; the present invention does not specifically limit the operation of evaporating silicon and carbon by a physical vapor deposition method, and those skilled in the art can make conventional selections; in the present invention, the temperature for evaporating silicon is, for example, 900 to 1300°C, the temperature for evaporating carbon is, for example, 1600 to 2200°C, and the time for evaporating silicon and carbon is, for example, 30 to 60 minutes; the present invention can obtain a silicon carbide coating (sealing layer) on the basis of the yttrium-doped hafnium carbide ultrahigh temperature coating by evaporating silicon and carbon on the surface in step (4), and finally annealing is performed using a Joule heat ultrafast synthesis process so that the obtained ultrahigh temperature ceramic coating consists of a yttrium-doped hafnium carbide ultrahigh temperature coating and a silicon carbide coating.

[0030] The present invention adopts a brush coating method to quickly introduce ultra-high temperature ceramic components (yttrium-doped hafnium carbide ultra-high temperature ceramic components) on the surface of a substrate with the help of hafnium-based MOFs and yttrium nitrate, wherein the presence of hafnium-based MOFs is conducive to the uniform dispersion of yttrium nitrate, ensuring the formation of yttrium-doped hafnium carbide ultra-high temperature ceramic components with uniform microstructure, and the pore structure of hafnium-based MOFs is conducive to the formation of specific nanoscale and / or microscale structures, which is conducive to optimizing the thermophysical properties and mechanical properties of the formed ceramic components, thereby improving the high temperature resistance, oxidation resistance and reusability of ceramic-based composite materials; the present invention finds , yttrium doping will change the crystal structure of hafnium carbide (HfC), reduce the formation of lattice defects by forming a solid solution, which is conducive to enhancing the thermal stability of ceramic-based composite materials in high temperature environments, and in high-temperature oxidizing environments, yttrium doping can form a dense yttrium oxide (Y2O3) protective layer, slow down the oxidation rate of hafnium carbide, and improve the oxidation resistance. In addition, yttrium doping can improve the thermal expansion coefficient matching of hafnium carbide (HfC), reduce thermal stress, and improve the thermal shock resistance of ceramic-based composite materials, thereby improving the service life of ceramic-based composite materials under multiple thermal cycles. The Joule heat ultrafast synthesis process adopted by the present invention can quickly improve the internal ceramic sintering degree of the coating and the bonding strength between the coating and the substrate, so as to effectively improve the protective effect of the coating on the substrate of the ceramic-based composite material, which is conducive to improving the high temperature resistance, oxidation resistance and reusability of the ceramic-based composite material.

[0031] According to some specific embodiments, the ceramic matrix composite material is subjected to high temperature annealing treatment in a vacuum atmosphere, and argon ions (Ar + ) bombard (etch) the surface of the annealed ceramic-based composite material to obtain a pretreated ceramic-based composite material; prepare an organic solution of hafnium-based metal-organic framework (MOFs) and yttrium nitrate Y(NO3)3, and use an ultrasonic-assisted method to evenly disperse the hafnium-based metal-organic framework (MOFs) and yttrium nitrate Y(NO3)3 to obtain an organic solution containing yttrium ion-doped hafnium-based metal-organic framework material; brush the organic solution onto the surface of the pretreated ceramic-based composite material, and slowly anneal it in a vacuum atmosphere to obtain a modified ceramic-based composite material; use a physical vapor deposition method to evaporate carbon and silicon onto the surface of the modified ceramic-based composite material, and after the evaporation is completed, use a Joule heat ultrafast synthesis process to high-temperature anneal the evaporated ceramic-based composite material to obtain a ceramic-based composite material protected by an ultra-high temperature ceramic coating (a ceramic-based composite material with an ultra-high temperature ceramic coating); the ceramic-based composite material protected by the ultra-high temperature ceramic coating prepared by the present invention has excellent high temperature resistance, oxidation resistance and reusability, and can be used for the preparation of thermal structural materials in the aerospace field.

[0032] According to some preferred embodiments, in step (1): at a vacuum pressure of ≤10 -6The annealing is carried out in a vacuum atmosphere at a pressure of 400 mbar and a temperature of ≥1000°C; in the present invention, the annealing time (holding time at the annealing temperature) in step (1) is, for example, 10 to 30 min; in step (1), the heating rate to the annealing temperature is, for example, 5 to 10°C / min.

[0033] According to some preferred embodiments, in step (1): when argon ions are used for bombardment, argon gas is introduced to the working pressure, and a glow discharge is generated after the power is turned on, and the argon gas is ionized into plasma to bombard the surface of the annealed ceramic matrix composite material; argon gas is introduced to the working pressure ≥5×10 -5 mbar; the bombardment voltage is 1.0-2.0keV, the bombardment current is 3-9mA, and the bombardment time is 5-15min.

[0034] According to some specific implementation methods, step (1) is: annealing the ceramic-based composite material in the vacuum chamber under vacuum atmosphere, then introducing argon gas into the vacuum chamber to the working pressure and applying high voltage (bombardment voltage) by turning on the power supply to generate glow discharge, and the argon gas is ionized into plasma to bombard the surface of the annealed ceramic-based composite material; wherein, when the vacuum pressure is ≤10 -6 mbar, annealing temperature ≥ 1000 ° C in vacuum atmosphere for 10 to 30 minutes; during argon ion bombardment, argon gas is introduced until the argon pressure (working pressure) is ≥ 5×10 -5 mbar, the bombardment voltage is 1.0-2.0 keV, the current is 3-9 mA, and the bombardment time is 5-15 min.

[0035] According to some preferred embodiments, in step (2), the preparation of the organic solution comprises the following sub-steps:

[0036] (a) using hafnium tetrachloride (HfCl4) as a hafnium source and terephthalic acid as an organic ligand, heating the reaction in N,N-dimethylformamide solvent to obtain a hafnium-based metal organic framework material (also referred to as hafnium-based MOFs); in the present invention, preferably, the mass amount of the N,N-dimethylformamide solvent is 8 to 20 times the sum of the mass amounts of hafnium tetrachloride and terephthalic acid;

[0037] (b) using ethanol (anhydrous ethanol) to uniformly disperse the hafnium-based metal organic framework material and yttrium nitrate under ultrasonic action to obtain an organic solution of the hafnium-based metal organic framework material doped with yttrium ions; in the present invention, preferably, the mass amount of the ethanol is 5 to 15 times the sum of the mass amounts of the hafnium-based metal organic framework material and yttrium nitrate; the ultrasonic action described in the present invention is to uniformly disperse the hafnium-based metal organic framework material and yttrium nitrate by ultrasonic treatment. The present invention does not specifically limit the conditions of the ultrasonic treatment, and those skilled in the art can routinely select the conditions. The frequency of the ultrasonic treatment is, for example, 20 to 40 kHz, and the time of the ultrasonic treatment is, for example, 40 to 60 min.

[0038] According to some preferred embodiments, in step (a): the molar ratio of the hafnium tetrachloride to the terephthalic acid is 1:(1.05-1.25) (e.g., 1:1.05, 1:1.1, 1:1.15, 1:1.2 or 1:1.25); and / or the temperature of the heating reaction is 120-150°C (e.g., 120°C, 130°C, 140°C or 150°C), and the time of the heating reaction is 20-40h (e.g., 20, 24, 28, 32, 36 or 40h).

[0039] According to some preferred embodiments, in step (b): the mass ratio of the yttrium nitrate to the hafnium-based metal organic framework material is 1:(5-10) (for example, 1:5, 1:6, 1:7, 1:8, 1:9 or 1:10); in the preparation of the organic solution containing the hafnium-based metal organic framework material doped with yttrium ions, preferably, the mass ratio of the yttrium nitrate to the hafnium-based metal organic framework material is 1:(5-10), which can ensure that yttrium nitrate provides sufficient yttrium ions and ensures that yttrium is properly doped in the hafnium carbide ultra-high temperature component, which is beneficial to improving the high temperature resistance, oxidation resistance and reusability of the ceramic-based composite material; the present invention finds that if the yttrium nitrate content is too high If the yttrium nitrate content is too high, the solid solution strengthening and antioxidant effects of yttrium cannot be fully exerted, and the protective oxide layer (Y2O3) of yttrium formed cannot be completely and effectively covered, which is not conducive to the effective improvement of the high temperature resistance and antioxidant properties of ceramic-based composites. If the yttrium nitrate content is too high, excessive yttrium ions may form local enrichment areas in the hafnium carbide matrix, resulting in lattice distortion or impurity generation, which will weaken the thermal physical properties of the coating, affect the integrity and density of the coating, and reduce the high temperature resistance and antioxidant properties of the ceramic-based composite. In addition, too high yttrium content may increase the difficulty of sintering the coating after brushing, and even cause cracking or peeling of the coating, affecting the bonding strength between the coating and the substrate.

[0040] According to some preferred embodiments, in step (3): the brush coating thickness of the organic solution is 100 to 300 μm; the annealing temperature is 500 to 1000°C (for example, 500°C, 600°C, 700°C, 800°C, 900°C or 1000°C); in the present invention, preferably, the annealing time (holding time at the annealing temperature) in step (3) is 30 to 90 min; and / or the heating rate to the annealing temperature is 5 to 10°C / min; in step (3), under a vacuum pressure of ≤10 -6 The annealing is performed in a vacuum atmosphere of mbar.

[0041] According to some preferred embodiments, in step (4): when evaporating silicon and carbon, the molar ratio of silicon to carbon is 1:(1.1-1.3) (eg, 1:1.1, 1:1.2 or 1:1.3).

[0042] According to some preferred embodiments, in step (4): the Joule heat ultrafast synthesis process is carried out in a Joule ultrafast heating device (Joule ultrafast heating device), the heating rate is 100-150°C / s (for example, 100°C / s, 110°C / s, 120°C / s, 130°C / s, 140°C / s or 150°C / s), and the annealing temperature is 1000-1600°C (for example, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C or 1600°C); in the present invention, preferably, the annealing time (holding time at the annealing temperature) in step (4) is 2-10 min.

[0043] In a second aspect, the present invention provides a ceramic-based composite material with an ultra-high temperature ceramic coating, which is prepared by the preparation method described in the first aspect of the present invention.

[0044] The present invention will be further described below by way of examples, but the protection scope of the present invention is not limited to these embodiments. The present invention may also have other various embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art may make various corresponding changes and deformations according to the present invention, but these corresponding changes and deformations shall all belong to the protection scope of the claims attached to the present invention. The experimental methods used in the following examples and comparative examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples and comparative examples, unless otherwise specified, can all be obtained from commercial channels.

[0045] Example 1

[0046] ①Preparation of pre-treated ceramic matrix composites: under vacuum pressure of 1×10 -6The ceramic matrix composite material (C / SiC composite material) placed in the vacuum chamber was annealed in a vacuum atmosphere of 1000 °C (annealing temperature 1000 °C, holding time at 1000 °C for 20 min, and heating rate to 1000 °C at 10 °C / min), and then argon was introduced into the vacuum chamber to a working pressure of 5×10 -5 mbar), and glow discharge is generated after the power is turned on and high voltage (bombardment voltage) is applied. Argon gas is ionized into plasma to bombard the surface of the annealed ceramic-based composite material to obtain a pretreated ceramic-based composite material; when bombarding, the bombardment voltage is 1.5 keV, the current is 6 mA, and the bombardment time is 10 min.

[0047] ② Preparation of modified ceramic-based composite materials: Using hafnium tetrachloride (HfCl4) as the hafnium source and terephthalic acid as the organic ligand, a heating reaction is carried out in N,N-dimethylformamide solvent to obtain a hafnium-based metal organic framework material, wherein the molar ratio of HfCl4 to terephthalic acid is 1:1.10, the mass amount of N,N-dimethylformamide solvent is 10 times the sum of the mass amounts of HfCl4 and terephthalic acid, the heating reaction temperature is 120°C, and the heating reaction time is 24h; the obtained hafnium-based metal organic framework is reacted with ethanol The organic framework material (hafnium-based MOFs) and yttrium nitrate Y(NO3)3 are uniformly dispersed under ultrasonic action to obtain an organic solution containing yttrium ion-doped hafnium-based metal organic framework material, wherein the mass ratio of Y(NO3)3 to hafnium-based MOFs is 1:10, and the mass amount of ethanol is 8 times the sum of the mass amounts of hafnium-based metal organic framework material and yttrium nitrate; the obtained organic solution is brushed onto the surface of the pretreated ceramic matrix composite material obtained in step ① (the brushing thickness is 150 μm), and placed in a vacuum pressure of 1×10 -6 The modified ceramic matrix composite material was obtained by slowly annealing in a vacuum atmosphere of mbar at a temperature of 800°C, a holding time of 60 minutes at 800°C, and a heating rate of 10°C / min to the annealing temperature.

[0048] ③ Preparation of ceramic-based composite materials with ultra-high temperature ceramic coatings: using a physical vapor deposition method to simultaneously evaporate silicon and carbon onto the surface of the modified ceramic-based composite material obtained in step ②, the molar ratio of silicon to carbon evaporation is 1:1.2, the silicon evaporation temperature is 1200°C, the carbon evaporation temperature is 1800°C, and the evaporation time is 30 minutes; after the evaporation is completed, the evaporated ceramic-based composite material is subjected to high-temperature annealing using a Joule heat ultrafast synthesis process to obtain a ceramic-based composite material with an ultra-high temperature ceramic coating; wherein the Joule heat ultrafast synthesis process is carried out in a Joule ultrafast heating device, the heating rate is 120°C / s, the annealing temperature is 1300°C, and the insulation time at 1300°C is 5 minutes.

[0049] The ceramic-based composite material with an ultra-high temperature ceramic coating prepared in this embodiment was subjected to performance tests, and its bending strength in an air atmosphere of 1450°C was measured to be 315 MPa, and the bending strength retention rate after 100 oxidation cycles in an air atmosphere of 1600°C was 73.1%; wherein, oxidation in an air atmosphere of 1600°C for 30 minutes and then natural cooling to room temperature was recorded as one oxidation cycle.

[0050] Example 2

[0051] ①Preparation of pre-treated ceramic matrix composites: under vacuum pressure of 1×10 -6 The ceramic matrix composite material (C / ZrC-SiC composite material) placed in the vacuum chamber was annealed in a vacuum atmosphere of mbar (annealing temperature 1000°C, holding time at 1000°C for 20 min, heating rate to annealing temperature 1000°C at 10°C / min), and then argon was introduced into the vacuum chamber to a working pressure (5×10 -5 mbar), and glow discharge is generated after the power is turned on and high voltage (bombardment voltage) is applied. Argon gas is ionized into plasma to bombard the surface of the annealed ceramic-based composite material to obtain a pretreated ceramic-based composite material; when bombarding, the bombardment voltage is 1.5 keV, the current is 6 mA, and the bombardment time is 10 min.

[0052] ② Preparation of modified ceramic-based composite materials: Using hafnium tetrachloride (HfCl4) as the hafnium source and terephthalic acid as the organic ligand, a heating reaction is carried out in N,N-dimethylformamide solvent to obtain a hafnium-based metal organic framework material, wherein the molar ratio of HfCl4 to terephthalic acid is 1:1.10, the mass amount of N,N-dimethylformamide solvent is 10 times the sum of the mass amounts of HfCl4 and terephthalic acid, the heating reaction temperature is 120°C, and the heating reaction time is 24h; the obtained hafnium-based metal organic framework is reacted with ethanol The organic framework material (hafnium-based MOFs) and yttrium nitrate Y(NO3)3 are uniformly dispersed under ultrasonic action to obtain an organic solution containing yttrium ion-doped hafnium-based metal organic framework material, wherein the mass ratio of Y(NO3)3 to hafnium-based MOFs is 1:10, and the mass amount of ethanol is 8 times the sum of the mass amounts of hafnium-based metal organic framework material and yttrium nitrate; the obtained organic solution is brushed onto the surface of the pretreated ceramic matrix composite material obtained in step ① (the brushing thickness is 150 μm), and placed in a vacuum pressure of 1×10 -6 The modified ceramic matrix composite material was obtained by slowly annealing in a vacuum atmosphere of mbar at a temperature of 800°C, a holding time of 60 minutes at 800°C, and a heating rate of 10°C / min to the annealing temperature.

[0053] ③ Preparation of ceramic-based composite materials with ultra-high temperature ceramic coatings: using a physical vapor deposition method to simultaneously evaporate silicon and carbon onto the surface of the modified ceramic-based composite material obtained in step ②, the molar ratio of silicon to carbon evaporation is 1:1.2, the silicon evaporation temperature is 1200°C, the carbon evaporation temperature is 1800°C, and the evaporation time is 30 minutes; after the evaporation is completed, the evaporated ceramic-based composite material is subjected to high-temperature annealing using a Joule heat ultrafast synthesis process to obtain a ceramic-based composite material with an ultra-high temperature ceramic coating; wherein the Joule heat ultrafast synthesis process is carried out in a Joule ultrafast heating device, the heating rate is 120°C / s, the annealing temperature is 1300°C, and the insulation time at 1300°C is 5 minutes.

[0054] The ceramic-based composite material with an ultra-high temperature ceramic coating prepared in this embodiment was subjected to performance tests, and its bending strength in an air atmosphere of 1450°C was measured to be 331 MPa, and the bending strength retention rate after 100 oxidation cycles in an air atmosphere of 1600°C was 76.9%; wherein, oxidation in an air atmosphere of 1600°C for 30 minutes and then natural cooling to room temperature was recorded as one oxidation cycle.

[0055] Example 3

[0056] ①Preparation of pre-treated ceramic matrix composites: under vacuum pressure of 1×10 -6 The ceramic matrix composite material (C / HfC-SiC composite material) placed in the vacuum chamber was annealed in a vacuum atmosphere of 1000 °C (annealing temperature 1000 °C, holding time at 1000 °C for 20 min, and heating rate to 1000 °C at 10 °C / min), and then argon was introduced into the vacuum chamber to a working pressure of 5×10 -5 mbar), and glow discharge is generated after the power is turned on and high voltage (bombardment voltage) is applied. Argon gas is ionized into plasma to bombard the surface of the annealed ceramic-based composite material to obtain a pretreated ceramic-based composite material; when bombarding, the bombardment voltage is 1.5 keV, the current is 6 mA, and the bombardment time is 10 min.

[0057] ② Preparation of modified ceramic-based composite materials: Using hafnium tetrachloride (HfCl4) as the hafnium source and terephthalic acid as the organic ligand, a heating reaction is carried out in N,N-dimethylformamide solvent to obtain a hafnium-based metal organic framework material, wherein the molar ratio of HfCl4 to terephthalic acid is 1:1.10, the mass amount of N,N-dimethylformamide solvent is 10 times the sum of the mass amounts of HfCl4 and terephthalic acid, the heating reaction temperature is 120°C, and the heating reaction time is 24h; the obtained hafnium-based metal organic framework is reacted with ethanol The organic framework material (hafnium-based MOFs) and yttrium nitrate Y(NO3)3 are uniformly dispersed under ultrasonic action to obtain an organic solution containing yttrium ion-doped hafnium-based metal organic framework material, wherein the mass ratio of Y(NO3)3 to hafnium-based MOFs is 1:10, and the mass amount of ethanol is 8 times the sum of the mass amounts of hafnium-based metal organic framework material and yttrium nitrate; the obtained organic solution is brushed onto the surface of the pretreated ceramic matrix composite material obtained in step ① (the brushing thickness is 150 μm), and placed in a vacuum pressure of 1×10 -6 The modified ceramic matrix composite material was obtained by slowly annealing in a vacuum atmosphere of mbar at a temperature of 800°C, a holding time of 60 minutes at 800°C, and a heating rate of 10°C / min to the annealing temperature.

[0058] ③ Preparation of ceramic-based composite materials with ultra-high temperature ceramic coatings: using a physical vapor deposition method to simultaneously evaporate silicon and carbon onto the surface of the modified ceramic-based composite material obtained in step ②, the molar ratio of silicon to carbon evaporation is 1:1.2, the silicon evaporation temperature is 1200°C, the carbon evaporation temperature is 1800°C, and the evaporation time is 30 minutes; after the evaporation is completed, the evaporated ceramic-based composite material is subjected to high-temperature annealing using a Joule heat ultrafast synthesis process to obtain a ceramic-based composite material with an ultra-high temperature ceramic coating; wherein the Joule heat ultrafast synthesis process is carried out in a Joule ultrafast heating device, the heating rate is 120°C / s, the annealing temperature is 1300°C, and the insulation time at 1300°C is 5 minutes.

[0059] The ceramic-based composite material with an ultra-high temperature ceramic coating prepared in this embodiment was subjected to performance tests, and its bending strength in an air atmosphere of 1450°C was measured to be 347 MPa, and the bending strength retention rate after 100 oxidation cycles in an air atmosphere of 1600°C was 79.5%; wherein, oxidation in an air atmosphere of 1600°C for 30 minutes and then natural cooling to room temperature was recorded as one oxidation cycle.

[0060] Example 4

[0061] Embodiment 4 is substantially the same as Embodiment 1, except that:

[0062] ② Preparation of modified ceramic-based composite materials: Using hafnium tetrachloride (HfCl4) as the hafnium source and terephthalic acid as the organic ligand, a heating reaction is carried out in N,N-dimethylformamide solvent to obtain a hafnium-based metal organic framework material, wherein the molar ratio of HfCl4 to terephthalic acid is 1:1.10, the mass amount of N,N-dimethylformamide solvent is 10 times the sum of the mass amounts of HfCl4 and terephthalic acid, the heating reaction temperature is 120°C, and the heating reaction time is 24h; the obtained hafnium-based metal organic framework is reacted with ethanol The organic framework material (hafnium-based MOFs) and yttrium nitrate Y(NO3)3 are uniformly dispersed under ultrasonic action to obtain an organic solution containing yttrium ion-doped hafnium-based metal organic framework material, wherein the mass ratio of Y(NO3)3 to hafnium-based MOFs is 1:20, and the mass amount of ethanol is 8 times the sum of the mass amounts of hafnium-based metal organic framework material and yttrium nitrate; the obtained organic solution is brushed onto the surface of the pretreated ceramic matrix composite material obtained in step ① (the brushing thickness is 150 μm), and placed in a vacuum pressure of 1×10 -6 The modified ceramic matrix composite material was obtained by slowly annealing in a vacuum atmosphere of mbar at a temperature of 800°C, a holding time of 60 minutes at 800°C, and a heating rate of 10°C / min to the annealing temperature.

[0063] The ceramic-based composite material with an ultra-high temperature ceramic coating prepared in this embodiment was subjected to performance tests, and its bending strength in an air atmosphere of 1450°C was measured to be 296 MPa, and the bending strength retention rate after 100 oxidation cycles in an air atmosphere of 1600°C was 66.3%; wherein, oxidation in an air atmosphere of 1600°C for 30 minutes and then natural cooling to room temperature was recorded as one oxidation cycle.

[0064] Example 5

[0065] Example 5 is substantially the same as Example 1, except that:

[0066] ② Preparation of modified ceramic-based composite materials: Using hafnium tetrachloride (HfCl4) as the hafnium source and terephthalic acid as the organic ligand, a heating reaction is carried out in N,N-dimethylformamide solvent to obtain a hafnium-based metal organic framework material, wherein the molar ratio of HfCl4 to terephthalic acid is 1:1.10, the mass amount of N,N-dimethylformamide solvent is 10 times the sum of the mass amounts of HfCl4 and terephthalic acid, the heating reaction temperature is 120°C, and the heating reaction time is 24h; the obtained hafnium-based metal The organic framework material (hafnium-based MOFs) and yttrium nitrate Y(NO3)3 are uniformly dispersed under ultrasonic action to obtain an organic solution containing yttrium ion-doped hafnium-based metal organic framework material, wherein the mass ratio of Y(NO3)3 to hafnium-based MOFs is 1:3, and the mass amount of ethanol is 8 times the sum of the mass amounts of hafnium-based metal organic framework material and yttrium nitrate; the obtained organic solution is brushed onto the surface of the pretreated ceramic matrix composite material obtained in step ① (the brushing thickness is 150 μm), and placed in a vacuum pressure of 1×10 -6 The modified ceramic matrix composite material was obtained by slowly annealing in a vacuum atmosphere of mbar at a temperature of 800°C, a holding time of 60 minutes at 800°C, and a heating rate of 10°C / min to the annealing temperature.

[0067] The ceramic-based composite material with an ultra-high temperature ceramic coating prepared in this embodiment was subjected to performance tests, and its bending strength in an air atmosphere of 1450°C was measured to be 294 MPa, and the bending strength retention rate after 100 oxidation cycles in an air atmosphere of 1600°C was 61.9%; wherein, oxidation in an air atmosphere of 1600°C for 30 minutes and then natural cooling to room temperature was recorded as one oxidation cycle.

[0068] Comparative Example 1

[0069] ①Preparation of pre-treated ceramic matrix composites: under vacuum pressure of 1×10 -6 The ceramic matrix composite material (C / SiC composite material) placed in the vacuum chamber was annealed in a vacuum atmosphere of 1000 °C (annealing temperature 1000 °C, holding time at 1000 °C for 20 min, and heating rate to 1000 °C at 10 °C / min), and then argon was introduced into the vacuum chamber to a working pressure of 5×10 -5 mbar), and glow discharge is generated after the power is turned on and high voltage (bombardment voltage) is applied. Argon gas is ionized into plasma to bombard the surface of the annealed ceramic-based composite material to obtain a pretreated ceramic-based composite material; when bombarding, the bombardment voltage is 1.5 keV, the current is 6 mA, and the bombardment time is 10 min.

[0070] ② Preparation of modified ceramic matrix composite materials: HfC nanopowder and yttrium nitrate Y(NO3)3 are uniformly dispersed with ethanol under ultrasonic action to obtain an organic solution containing yttrium ion-doped HfC powder, wherein the mass ratio of Y(NO3)3 to HfC nanopowder is 1:10, and the mass amount of ethanol is 8 times the sum of the mass amounts of HfC nanopowder and yttrium nitrate; the obtained organic solution is brushed onto the surface of the pretreated ceramic matrix composite material obtained in step ① (the brushing thickness is 150 μm), and placed in a vacuum pressure of 1×10 -6 The modified ceramic matrix composite material was obtained by slowly annealing in a vacuum atmosphere of mbar at a temperature of 800°C, a holding time of 60 minutes at 800°C, and a heating rate of 10°C / min to the annealing temperature.

[0071] ③ Preparation of ceramic-based composite materials with ultra-high temperature ceramic coatings: using a physical vapor deposition method to simultaneously evaporate silicon and carbon onto the surface of the modified ceramic-based composite material obtained in step ②, the molar ratio of silicon to carbon evaporation is 1:1.2, the silicon evaporation temperature is 1200°C, the carbon evaporation temperature is 1800°C, and the evaporation time is 30 minutes; after the evaporation is completed, the evaporated ceramic-based composite material is subjected to high-temperature annealing using a Joule heat ultrafast synthesis process to obtain a ceramic-based composite material with an ultra-high temperature ceramic coating; wherein the Joule heat ultrafast synthesis process is carried out in a Joule ultrafast heating device, the heating rate is 120°C / s, the annealing temperature is 1300°C, and the insulation time at 1300°C is 5 minutes.

[0072] The ceramic-based composite material with ultra-high temperature ceramic coating prepared in this comparative example was subjected to performance testing, and its bending strength in an air atmosphere of 1450°C was measured to be 235 MPa, and the bending strength retention rate after 100 oxidation cycles in an air atmosphere of 1600°C was 52.8%; wherein, oxidation in an air atmosphere of 1600°C for 30 minutes and then natural cooling to room temperature was recorded as one oxidation cycle.

[0073] Comparative Example 2

[0074] ①Preparation of pre-treated ceramic matrix composites: under vacuum pressure of 1×10 -6 The ceramic matrix composite material (C / SiC composite material) placed in the vacuum chamber was annealed in a vacuum atmosphere of 1000 °C (annealing temperature 1000 °C, holding time at 1000 °C for 20 min, and heating rate to 1000 °C at 10 °C / min), and then argon was introduced into the vacuum chamber to a working pressure of 5×10 -5mbar), and glow discharge is generated after the power is turned on and high voltage (bombardment voltage) is applied. Argon gas is ionized into plasma to bombard the surface of the annealed ceramic-based composite material to obtain a pretreated ceramic-based composite material; when bombarding, the bombardment voltage is 1.5 keV, the current is 6 mA, and the bombardment time is 10 min.

[0075] ② Preparation of modified ceramic-based composite materials: Using hafnium tetrachloride (HfCl4) as the hafnium source and terephthalic acid as the organic ligand, a heating reaction is carried out in N,N-dimethylformamide solvent to obtain a hafnium-based metal organic framework material, wherein the molar ratio of HfCl4 to terephthalic acid is 1:1.10, the mass amount of N,N-dimethylformamide solvent is 10 times the sum of the mass amounts of HfCl4 and terephthalic acid, the heating reaction temperature is 120°C, and the heating reaction time is 24h; the obtained hafnium-based metal organic framework is reacted with ethanol The organic framework material (hafnium-based MOFs) and yttrium nitrate Y(NO3)3 are uniformly dispersed under ultrasonic action to obtain an organic solution containing yttrium ion-doped hafnium-based metal organic framework material, wherein the mass ratio of Y(NO3)3 to hafnium-based MOFs is 1:10, and the mass amount of ethanol is 8 times the sum of the mass amounts of hafnium-based metal organic framework material and yttrium nitrate; the obtained organic solution is brushed onto the surface of the pretreated ceramic matrix composite material obtained in step ① (the brushing thickness is 150 μm), and placed in a vacuum pressure of 1×10 -6 The modified ceramic matrix composite material was obtained by slowly annealing in a vacuum atmosphere of mbar at a temperature of 800°C, a holding time of 60 minutes at 800°C, and a heating rate of 10°C / min to the annealing temperature.

[0076] ③ Preparation of ceramic-based composite materials with ultra-high temperature ceramic coating: Use physical vapor deposition method to simultaneously evaporate silicon and carbon on the surface of the modified ceramic-based composite material obtained in step ②, the molar ratio of silicon to carbon evaporation is 1:1.2, the temperature of silicon evaporation is 1200℃, the temperature of carbon evaporation is 1800℃, and the evaporation time is 30min; after the evaporation, the evaporated ceramic-based composite material is subjected to high-temperature annealing to obtain a ceramic-based composite material with ultra-high temperature ceramic coating; wherein the high-temperature annealing temperature is 1300℃, the holding time at 1300℃ is 5min, and the heating rate to 1300℃ is 10℃ / min.

[0077] The ceramic-based composite material with ultra-high temperature ceramic coating prepared in this comparative example was subjected to performance testing, and its bending strength in an air atmosphere of 1450°C was measured to be 261 MPa, and the bending strength retention rate after 100 oxidation cycles in an air atmosphere of 1600°C was 57.9%; wherein, oxidation in an air atmosphere of 1600°C for 30 minutes and then natural cooling to room temperature was recorded as one oxidation cycle.

[0078] Comparative Example 3

[0079] ①Preparation of pre-treated ceramic matrix composites: under vacuum pressure of 1×10 -6 The ceramic matrix composite material (C / SiC composite material) placed in the vacuum chamber was annealed in a vacuum atmosphere of 1000 °C (annealing temperature 1000 °C, holding time at 1000 °C for 20 min, and heating rate to 1000 °C at 10 °C / min), and then argon was introduced into the vacuum chamber to a working pressure of 5×10 -5 mbar), and glow discharge is generated after the power is turned on and high voltage (bombardment voltage) is applied. Argon gas is ionized into plasma to bombard the surface of the annealed ceramic-based composite material to obtain a pretreated ceramic-based composite material; when bombarding, the bombardment voltage is 1.5 keV, the current is 6 mA, and the bombardment time is 10 min.

[0080] ② Preparation of a ceramic-based composite material with a ceramic coating: using a physical vapor deposition method to simultaneously evaporate silicon and carbon onto the surface of the pretreated ceramic-based composite material obtained in step ①, the molar ratio of silicon to carbon evaporation is 1:1.2, the silicon evaporation temperature is 1200°C, the carbon evaporation temperature is 1800°C, and the evaporation time is 30 minutes; after the evaporation is completed, the evaporated ceramic-based composite material is subjected to high-temperature annealing using a Joule heat ultrafast synthesis process to obtain a ceramic-based composite material with a ceramic coating; wherein the Joule heat ultrafast synthesis process is carried out in a Joule ultrafast heating device, the heating rate is 120°C / s, the annealing temperature is 1300°C, and the insulation time at 1300°C is 5 minutes.

[0081] The ceramic-based composite material with ceramic coating obtained in this comparative example was subjected to performance testing, and its bending strength in an air atmosphere at 1450°C was measured to be 218 MPa, and the bending strength retention rate after 100 oxidation cycles in an air atmosphere at 1600°C was 47.2%; wherein, oxidation in an air atmosphere at 1600°C for 30 minutes and then natural cooling to room temperature was recorded as one oxidation cycle.

[0082] Comparative Example 4

[0083] ①Preparation of pre-treated ceramic matrix composites: under vacuum pressure of 1×10 -6 The ceramic matrix composite material (C / SiC composite material) placed in the vacuum chamber was annealed in a vacuum atmosphere of 1000 °C (annealing temperature 1000 °C, holding time at 1000 °C for 20 min, and heating rate to 1000 °C at 10 °C / min), and then argon was introduced into the vacuum chamber to a working pressure of 5×10 -5mbar), and glow discharge is generated after the power is turned on and high voltage (bombardment voltage) is applied. Argon gas is ionized into plasma to bombard the surface of the annealed ceramic-based composite material to obtain a pretreated ceramic-based composite material; when bombarding, the bombardment voltage is 1.5 keV, the current is 6 mA, and the bombardment time is 10 min.

[0084] ② Preparation of ceramic matrix composite material with ceramic coating: using chemical vapor deposition method to deposit SiC coating on the surface of the pretreated ceramic matrix composite material obtained in step ①.

[0085] The ceramic-based composite material with ceramic coating prepared in this comparative example was subjected to performance testing, and its flexural strength in an air atmosphere at 1450°C was measured to be 195 MPa, and the flexural strength retention rate after 100 oxidation cycles in an air atmosphere at 1600°C was 32.5%; wherein, oxidation in an air atmosphere at 1600°C for 30 minutes and then natural cooling to room temperature was recorded as one oxidation cycle.

[0086] Comparative Example 5

[0087] Comparative Example 5 is substantially the same as Example 1, except that:

[0088] ② Preparation of modified ceramic-based composite materials: using hafnium tetrachloride (HfCl4) as a hafnium source and terephthalic acid as an organic ligand, a heating reaction is carried out in an N,N-dimethylformamide solvent to obtain a hafnium-based metal organic framework material, wherein the molar ratio of HfCl4 to terephthalic acid is 1:1.10, the mass amount of N,N-dimethylformamide solvent is 10 times the sum of the mass amounts of HfCl4 and terephthalic acid, the heating reaction temperature is 120°C, and the heating reaction time is 24 hours; using ethanol to uniformly disperse the obtained hafnium-based metal organic framework material (hafnium-based MOFs) under ultrasonic action to obtain an organic solution containing the hafnium-based metal organic framework material, and the mass amount of ethanol is 8 times the mass amount of the hafnium-based metal organic framework material; the obtained organic solution is brushed onto the surface of the pretreated ceramic-based composite material obtained in step ① (the brushing thickness is 150 μm), and placed in a vacuum pressure of 1×10 -6 The modified ceramic matrix composite material was obtained by slowly annealing in a vacuum atmosphere of mbar at a temperature of 800°C, a holding time of 60 minutes at 800°C, and a heating rate of 10°C / min to the annealing temperature.

[0089] The ceramic-based composite material with ultra-high temperature ceramic coating prepared in this comparative example was subjected to performance testing, and its bending strength in an air atmosphere of 1450°C was measured to be 242 MPa, and the bending strength retention rate after 100 oxidation cycles in an air atmosphere of 1600°C was 54.3%; wherein, oxidation in an air atmosphere of 1600°C for 30 minutes and then natural cooling to room temperature was recorded as one oxidation cycle.

[0090] Comparative Example 6

[0091] Comparative Example 6 is substantially the same as Example 1, except that:

[0092] ①Preparation of pre-treated ceramic matrix composites: under vacuum pressure of 1×10 -6 The ceramic matrix composite material (C / SiC composite material) placed in a vacuum chamber was annealed under a vacuum atmosphere of mbar (annealing temperature 1000°C, holding time at 1000°C for 20 min, and heating rate to the annealing temperature of 1000°C was 10°C / min) to obtain a pretreated ceramic matrix composite material.

[0093] The ceramic-based composite material with ultra-high temperature ceramic coating obtained in this comparative example was subjected to performance testing, and its bending strength in an air atmosphere of 1450°C was measured to be 258 MPa, and the bending strength retention rate after 100 oxidation cycles in an air atmosphere of 1600°C was 42.1%; wherein, oxidation in an air atmosphere of 1600°C for 30 minutes and then natural cooling to room temperature was recorded as one oxidation cycle.

[0094] In this comparative example, the annealed ceramic-based composite material was not bombarded with argon ions, resulting in a weaker bonding force between the pretreated ceramic-based composite material and the subsequent coating, ultimately leading to a lower high-temperature flexural strength of the prepared ceramic-based composite material, and insufficient thermal shock resistance during cyclic oxidation, resulting in relatively poor performance.

[0095] In the present invention, the performance test results of the ceramic-based composite materials finally prepared in various embodiments and comparative examples are shown in Table 1.

[0096] Table 1

[0097]

[0098]

[0099] Parts of the present invention that are not described in detail are well known to those skilled in the art.

[0100] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a ceramic-based composite material having an ultra-high temperature ceramic coating, characterized in that: The method comprises the following steps: (1) annealing the ceramic matrix composite material in a vacuum atmosphere, and then bombarding the surface of the annealed ceramic matrix composite material with argon ions to obtain a pretreated ceramic matrix composite material; (2) preparing an organic solution containing a hafnium-based metal organic framework material doped with yttrium ions; (3) applying an organic solution to the surface of the pretreated ceramic-based composite material and annealing the pretreated ceramic-based composite material in a vacuum atmosphere to obtain a modified ceramic-based composite material; (4) Silicon and carbon are evaporated onto the surface of the modified ceramic matrix composite material using a physical vapor deposition method, and then annealed using a Joule heat ultrafast synthesis process to obtain a ceramic matrix composite material with an ultrahigh temperature ceramic coating.

2. The preparation method according to claim 1, characterized in that: In step (1): At vacuum pressure ≤10 -6 Annealing is carried out in a vacuum atmosphere with a pressure of 1000 mbar and a temperature of ≥1000°C.

3. The preparation method according to claim 1, characterized in that: In step (1): When argon ions are used for bombardment, argon gas is introduced to the working pressure, and a glow discharge is generated after the power is turned on. The argon gas is ionized into plasma to bombard the surface of the annealed ceramic-based composite material. Introduce argon gas until the working pressure is ≥5×10 -5 mbar; The bombardment voltage is 1.0-2.0 keV, the bombardment current is 3-9 mA, and the bombardment time is 5-15 min.

4. The preparation method according to claim 1, characterized in that: In step (2), the preparation of the organic solution comprises the following sub-steps: (a) using hafnium tetrachloride as a hafnium source and terephthalic acid as an organic ligand, heating the mixture in N,N-dimethylformamide solvent to obtain a hafnium-based metal organic framework material; (b) using ethanol to uniformly disperse the hafnium-based metal organic framework material and yttrium nitrate under ultrasonic action to obtain an organic solution containing the hafnium-based metal organic framework material doped with yttrium ions.

5. The preparation method according to claim 4, characterized in that: In step (a): The molar ratio of the hafnium tetrachloride to the terephthalic acid is 1:(1.05-1.25); and / or The temperature of the heating reaction is 120-150° C., and the time of the heating reaction is 20-40 hours.

6. The preparation method according to claim 4, characterized in that: In step (b): The mass ratio of the yttrium nitrate to the hafnium-based metal organic framework material is 1:(5-10).

7. The preparation method according to claim 1, characterized in that: In step (3): The brush coating thickness of the organic solution is 100 to 300 μm; The annealing temperature is 500-1000° C. The holding time at the annealing temperature is 30 to 90 minutes; and / or The heating rate to the annealing temperature is 5 to 10°C / min.

8. The preparation method according to claim 1, characterized in that: In step (4): When silicon and carbon are evaporated, the molar ratio of silicon to carbon is 1:(1.1 to 1.3).

9. The preparation method according to claim 1, characterized in that: In step (4): The Joule heat ultrafast synthesis process is carried out in a Joule ultrafast heating device, with a heating rate of 100-150° C. / s, an annealing temperature of 1000-1600° C., and a holding time of 2-10 minutes at the annealing temperature.

10. A ceramic matrix composite material with an ultra-high temperature ceramic coating, characterized in that: The preparation method is described in any one of claims 1 to 9.